Intellectual Property Rights and Global Climate Change: Toward Resolving an Apparent Dilemma. Issue 3 (1st September 2016) - Biddle, Justin B.
Abstract: This paper addresses an apparent dilemma that must be resolved in order to respond ethically to global climate change. The dilemma can be presented as follows. Responding ethically to global climate change requires technological innovation that is accessible to everyone, including inhabitants of the least developed countries. Technological innovation, according to many, requires strong intellectual property protection, but strong intellectual property protection makes it highly unlikely that patent-protected technologies will be accessible to developing countries at affordable prices. Given this, responding ethically to global climate change is highly unlikely. I argue that this apparent dilemma – which I call 'the patent dilemma in global climate change' – should be taken seriously. I discuss a number of possibilities for resolving it, and I argue that any acceptable strategy must satisfy the criteria of near-term feasibility and non-paternalism. Finally, I propose a multi-pronged, multi-tiered strategy that meets these conditions.